The Eurosystem Household Finance and Consumption Survey - Results from the first wave (European Central Bank (ECB), 2013)
This report summarises key stylised facts from the first wave of the Eurosystem Household Finance and Consumption Survey, which provides household-level data collected in a harmonised way in 15 euro area countries for a sample of more than 62,000 households. The report presents results on household assets and liabilities, income, and indicators of consumption and credit constraints.
Keywords: D12; D14; D31; 330; assets; Consumption; financial pressure; household-level data; liabilities; wealth